A Comparative Legal Analysis of Freedom of Belief and Worship in Turkey - UGUR, Hakan; GÜLOĞLU, Nazife Vildan; Guloglu, Yavuz (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
Freedom of Belief and Freedom of Worship are interrelated and complementary freedoms. While belief primarily concerns the internal aspect of an individual, their spirit and worship can be seen as the manifestation of belief, transitioning from the abstract to the tangible. Freedom of belief and worship are among the inalienable fundamental rights established in national, regional, and international human rights documents. Recognised as one of the core values of a democratic society, freedom of belief is considered a fundamental right that cannot be restricted, even in times of war or emergency. The scope of these rights and freedoms, as enshrined in the constitutions of modern societies, has expanded over time in favour of liberties through legislative regulations and judicial rulings. Generally, in the decisions of the Turkish Constitutional Court and the European Court of Human Rights, to which Turkey is a party, it is emphasised that the internal aspect of freedom of belief is an inseparable part of one’s personality, making this freedom non-restrictable. However, it is difficult to assert that freedom of worship, which serves as an outward expression of this liberty, is fully guaranteed by the legal system, as it is acknowledged that this freedom can be restricted in line with the requirements of a democratic society. Given that the boundaries of freedom of belief and worship cannot be distinctly defined and that separating these two domains is highly complex, it must be recognised that any intervention or limitation on freedom of worship inevitably impacts freedom of belief. This study will examine international legal regulations on freedom of belief and worship, constitutional provisions, and the decisions of the European Court of Human Rights and the Constitutional Court on this matter. Additionally, progress made in Turkey, along with challenges and shortcomings encountered in practice, will be addressed, and potential solutions will be offered. The topic will also be compared from a religious perspective, assessing the role of religion concerning these freedoms.